If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12y + -12 = 5y + -8 Reorder the terms: -12 + 12y = 5y + -8 Reorder the terms: -12 + 12y = -8 + 5y Solving -12 + 12y = -8 + 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. -12 + 12y + -5y = -8 + 5y + -5y Combine like terms: 12y + -5y = 7y -12 + 7y = -8 + 5y + -5y Combine like terms: 5y + -5y = 0 -12 + 7y = -8 + 0 -12 + 7y = -8 Add '12' to each side of the equation. -12 + 12 + 7y = -8 + 12 Combine like terms: -12 + 12 = 0 0 + 7y = -8 + 12 7y = -8 + 12 Combine like terms: -8 + 12 = 4 7y = 4 Divide each side by '7'. y = 0.5714285714 Simplifying y = 0.5714285714
| 6b^2-18b-60=0 | | 4(y+1)=-81 | | 14x+28=0 | | 18-86+z=20 | | x^2-2x-10=2x+11 | | b-3=15 | | 6a=96 | | 2x-5-5x=16 | | 17.5=5s | | x^2+25x-8400=0 | | 4(x-5)=54 | | 4(x-7)=2x+6 | | 7(x+5)=-28 | | 3+4p-p=15 | | 11.384+3.41b=2.5b-1.2(7.6-2.7b) | | 9x-(4x-6)=17+2(2x+8) | | 12y-2y=-40 | | x-6/5=2 | | 3x-13=4x-16 | | -(9-3x)-(4+2x)-4=-(2-5x)-5 | | -(9-3x)-(4+2)-4=-(2-5x)-5 | | -2=34-18-54 | | -38.477-1.09x=2.7(x-7.9)+9.4x | | 3(x-5)+7x-16=4(x+2)-10 | | 2(x-3)=6(x+5) | | -10=-19+7m | | 125-v^3= | | 5x-8+2x=3x-16 | | 2(-1+6x)=-38 | | 2(-1+6x)=-38 | | 3r^2+24r+36=0 | | 6x+5+4x-2=8x+21 |